1990
DOI: 10.1104/pp.93.4.1383
|View full text |Cite
|
Sign up to set email alerts
|

Slow Inactivation of Ribulosebisphosphate Carboxylase during Catalysis Is Not Due to Decarbamylation of the Catalytic Site

Abstract: An investigation was made of the proposal that the slow inactivation of ribulosebisphosphate carboxylase (Rubisco) activity, which occurs during in vitro assays, is due to decarbamylation of the enzyme. The level of carbamylation was compared with catalytic activity during assay conditions in which activity was both increasing and decreasing. Carbamylation level was measured using the reaction-intermediate analogue 2'-carboxy-D-arabinitol-1,5-bisphosphate (carboxyarabinitol-P2). A dual isotope procedure was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 22 publications
1
35
1
Order By: Relevance
“…Glycerate presumably is formed by dephosphorylation of a portion of the major product P-glycerate by traces of phosphatases contaminating the enzyme preparations. The large enzyme concentrations and extended assay periods necessitated by the feeble activity of L 8 system. The partitioning ratios observed were 0.61 Ϯ 0.05% (n ϭ 6) and 0.71 Ϯ 0.05% (n ϭ 5) for L 8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Glycerate presumably is formed by dephosphorylation of a portion of the major product P-glycerate by traces of phosphatases contaminating the enzyme preparations. The large enzyme concentrations and extended assay periods necessitated by the feeble activity of L 8 system. The partitioning ratios observed were 0.61 Ϯ 0.05% (n ϭ 6) and 0.71 Ϯ 0.05% (n ϭ 5) for L 8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The large enzyme concentrations and extended assay periods necessitated by the feeble activity of L 8 system. The partitioning ratios observed were 0.61 Ϯ 0.05% (n ϭ 6) and 0.71 Ϯ 0.05% (n ϭ 5) for L 8 (Fig. 1A) and L 8 S 8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been many proposals that ribulose-P2 binds more tightly to the uncarbamylated enzyme (E) than to the carbamylated, metal-complexed form (ECM), thus promoting decarbamylation with concomitant loss of activity (11,12,15). This plausible hypothesis has been tested, and found to be incorrect, in the work described in the second paper ofthis series (8). (b) Readily reversible binding of ribulose-P2 to a regulatory site, different from the catalytic site, causing a reduction in activity of the fully carbamylated enzyme has been proposed by Yokota and Kitaoka (26) who suggested that fallover is a natural phenomenon, reflecting in vivo control of Rubisco activity by ribulose-P2.…”
mentioning
confidence: 99%